Natural Compounds and Glutathione: Beyond Mere Antioxidants - Claudia Di Giacomo; Giuseppe Antonio Malfa; Barbara Tomasello; Simone Bianchi; Rosaria Acquaviva (MDPI AG, 2023)
The tripeptide glutathione plays important roles in many cell processes, including differentiation, proliferation, and apoptosis; in fact, disorders in glutathione homeostasis are involved both in the etiology and in the progression of several human diseases, including cancer. Natural compounds have been found to modulate glutathione levels and function beyond their role as mere antioxidants. For example, certain compounds can upregulate the expression of glutathione-related enzymes, increase the availability of cysteine, the limiting amino acid for glutathione synthesis, or directly interact with glutathione and modulate its function. These compounds may have therapeutic potential in a variety of disease states where glutathione dysregulation is a contributing factor. On the other hand, flavonoids' potential to deplete glutathione levels could be significant for cancer treatment. Overall, while natural compounds may have potential therapeutic and/or preventive properties and may be able to increase glutathione levels, more research is needed to fully understand their mechanisms of action and their potential benefits for the prevention and treatment of several diseases. In this review, particular emphasis will be placed on phytochemical compounds belonging to the class of polyphenols, terpenoids, and glucosinolates that have an impact on glutathione-related processes, both in physiological and pathological conditions. These classes of secondary metabolites represent the most food-derived bioactive compounds that have been intensively explored and studied in the last few decades.